2019
DOI: 10.3390/info10050177
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Virtual Reality-Based Game Approach for Supporting Sensory Processing Disorders Treatment

Abstract: Serious games for health are those that are not aimed solely at entertainment, but rather at supporting health treatments. In this paper, we develop and assess the proposal of a Virtual Reality (VR) game aimed at supporting Sensory Processing Disorder (SPD) treatment. SPD is a condition which affects the integration and processing of the various stimuli coming from inside and outside of the body and its treatment involves providing patients with controlled sensory stimuli. Our goal is to investigate whether a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…For example, Tuveri and colleagues designed Rift-a-bike to engage a general audience in cycling-based exercise [ 49 ] while Eisapour and colleagues focused on exercise for people with dementia [ 74 ] . Other health contexts ranged from addressing sensory disorders [ 70 ] to cognitive functioning [ 53 ]. Overall, these contexts are consistent with applications found in the broader health VR field, which includes non-game and non-HMD applications [ 78 – 80 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Tuveri and colleagues designed Rift-a-bike to engage a general audience in cycling-based exercise [ 49 ] while Eisapour and colleagues focused on exercise for people with dementia [ 74 ] . Other health contexts ranged from addressing sensory disorders [ 70 ] to cognitive functioning [ 53 ]. Overall, these contexts are consistent with applications found in the broader health VR field, which includes non-game and non-HMD applications [ 78 – 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, the upper-limb stroke rehabilitation game, "A Priest in the Air", sets the player traveling through different countries in an air balloon to reach a king, using arm movements to guide the balloon into point-scoring objects [60]. Other games simply involved aesthetics in terms of thematic setting and goals [62,70,76]. One game used pedaling mechanics to navigate a city and capture unique creatures [62] while another used the mechanics of capturing a flying butterfly to elicit head movements for neck rehabilitation [66].…”
Section: Game Design In Hmd-vr Health Gamesmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of each individual sensory channel and multisensory integration to perception and movement can be assessed and stimulated based on the individual needs and functioning of the child and adult. Recent studies further suggested that headsets can stimulate multiple sensory systems in people with sensory processing disorders [ 27 ], promote multisensory integration in cases of vestibular disorders [ 28 ], and provide three-dimensional auditory stimuli in a play context, thereby reducing perceived anxiety toward target auditory stimuli in adolescents with ASD [ 29 ]. This corpus of studies indicates that stimulation via IVR might be relevant for people with sensory processing difficulties over and above the specific diagnostic label they were ascribed.…”
Section: Keep the Senses In Mindmentioning
confidence: 99%
“…Some researchers have received positive feedback from occupational therapists who used customizable HMD-games for children with sensory processing disorders. Different games were designed to stimulate several sensory systems through manipulation of visual properties (complexity of the environment, object color and size), audio volume and effects, and vestibular input (e.g., speed of participant’s roller-coaster cart) ( Rossi et al, 2019 ). However, the effects on participants’ sensorimotor functioning were not directly measured.…”
Section: Ivr and Sensorimotor Functioning In Asdmentioning
confidence: 99%